A 3D porous interconnected NaVPO4F/C network: preparation and performance for Na-ion batteries1. Issue 50 (4th June 2015) - Xu, Maowen; Cheng, Chuan-Jun; Sun, Qiang-Qiang; Bao, Shu-Juan; Niu, Yu-Bin; He, Hong; Li, Yutao; Song, Jie
<x xml:space="preserve">Abstract</x> 3D porous interconnected NaVPO4F/C network is fabricated by a hydrothermal method and sintering process. As a Na-ion battery cathode material, it delivers a good electrochemical performance.